Amipurimycin: Total Synthesis of the Proposed Structures and Diastereoisomers. Issue 11 (12th February 2018) - Wang, Shengyang; Sun, Jiansong; Zhang, Qingju; Cao, Xin; Zhao, Yachen; Tang, Gongli; Yu, Biao
Abstract: The proposed diastereoisomers (1 a –d ) together with their C8′‐epimers (1 e –h ) of amipurimycin, a unique antifungal peptidyl nucleoside antibiotic, have been synthesized for the first time. The synthetic approach is efficient and stereodivergent, and features a stereoselective aldol condensation to build the branched C9 sugar amino acid skeleton and a regio‐ and stereocontrolled gold(I)‐catalyzed N‐glycosylation to furnish the purine nucleoside. Analysis of the NMR data suggests that the previously assigned configuration of the tertiary C3′ in amipurimycin should be of opposite configuration. Abstract : All in the configuration : The proposed diastereoisomers and the relevant C8′ epimers of amipurimycin, a unique peptidyl nucleoside antibiotic, have been synthesized for the first time. Analysis of the NMR data suggests that the previously assigned configuration of the tertiary C3′ in amipurimycin should be in fact of opposite configuration.